ChemInform Abstract: A Novel Domino Condensation—Intramolecular Nucleophilic Cyclization Approach Toward Annulated Imidazo‐Pyrrolopyridines. Issue 12 (March 2016) - Voskressensky, Leonid G.; Storozhenko, Olga A.; Festa, Alexey A.; Khrustalev, Victor N.; Dang, Thi Tuyet Anh; Nguyen, Van Tuyen; Varlamov, Alexey V.
Abstract: A facile protocol is developed for the base‐promoted domino reaction of 6‐azaindole salts (I) with aldehydes (II) to form the title compounds (III) in moderate yields.